The impact of liquidity risk on the market value of the shares of Saudi commercial banks, a standard study using cross-sectional data models Panel for the period (2010-202( - djani, amina; messaitfa, abdellatif (Journal of Excellence for Economics and Management Research, 2022)
This study aimed to demonstarte the impact of liquidity risk on the market value of the shares of commercial banks listed in the Saudi stok market tadaw . The study was conducted on 10 commercial banks during the period 2010 to 2020,using the Panal data model, the study concluded that thers is an inverse relationship between liquidity risks and the market value of shares in the banks under study. Invest in these banks